m = (y2-y1)/(x2-x1)
m = (6-4)/(4-0)
m = 2/4
y = mx + c
6 = (2/4)(4) + c
c = 4
Thus, the equation is y = (2/4)x +4
Answer:
-1 and -4
Step-by-step explanation:
-1 + -4 = -5
-1 times -4 = 4
give brainiest please!
hope this helps ;)
Answer: Here is the explanation. also it it +3y not -3y
Step-by-step explanation:
x+y+4+2y+1=x+3y+5 because
2y+y=3y
so now you have x+3y+4+1
4+1=5
now you have: x+3y+5
if you do not understand, What i am trying to say is, you need to add all of the same things.
Answer:
B
Step-by-step explanation:
The y-intercept is 2 and the slope is 1. Therefore, the answer is 2y=x. :)